(untitled) (Research, Society and Development, 2021)
The present study aims to assess the prevalence of dyslipidemia and estimate cardiovascular risk according to more accurate biochemical indicators in adolescents, according to nutritional status. This is a cross-sectional study conducted with 807 adolescents from public schools, of both sexes, aged 10 to 17 years. The nutritional status was classified according to the body mass index. Dyslipidemia was considered the presence of increased levels in at least one of the parameters of the lipid profile: triglycerides (TG), total cholesterol and high (HDL-c) and low density (LDL-c) fractions. Cardiovascular risk was estimated by calculating Castelli Index I (CI-I) and II (CI-II), TG/HDL-c and non-HDL-c. Data were analyzed by Poisson regression with robust estimates of variance at 5% significance level. The median age was 13 (12-14) years, of which 57.7% were female. A 32% prevalence of excess weight was found. Excess weight was associated with cardiovascular risk in adolescents, and CI-II (PR: 2.75; 95%CI: 1.77-4.27; p<0.001) was the marker with the highest prevalence in the excess weight group, followed by CI-I (PR: 1.87; 95%CI: 1.56-2.22; p<0.001). It was possible to conclude that the use of IC-I and II had a higher prevalence than lipid markers analyzed alone and, therefore, are more robust predictors of cardiovascular risk in excess weight adolescents.